2021
DOI: 10.3389/fvets.2021.637580
|View full text |Cite|
|
Sign up to set email alerts
|

A Meta-Analysis of the Effect of Bacillus Calmette-Guérin Vaccination Against Bovine Tuberculosis: Is Perfect the Enemy of Good?

Abstract: More than 50 million cattle are likely exposed to bovine tuberculosis (bTB) worldwide, highlighting an urgent need for bTB control strategies in low- and middle-income countries (LMICs) and other regions where the disease remains endemic and test-and-slaughter approaches are unfeasible. While Bacillus Calmette-Guérin (BCG) was first developed as a vaccine for use in cattle even before its widespread use in humans, its efficacy against bTB remains poorly understood. To address this important knowledge gap, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 85 publications
3
35
1
Order By: Relevance
“…Similar to the study in New Zealand, the infection pressure was low as contact challenge was conducted in a herd with bTB prevalence of 24%. Although the efficacy value recorded by the present study was within the range of BCG efficacy (0 and 75%) reported from experimental studies and field trials in cattle by different researchers from different countries [reviewed by ( 19 , 21 )], the use of 100% positive seeders as a source of infection could have contributed to the lower efficacy value recorded, as compared with those studies conducted in Mexico, New Zealand, and Chile.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…Similar to the study in New Zealand, the infection pressure was low as contact challenge was conducted in a herd with bTB prevalence of 24%. Although the efficacy value recorded by the present study was within the range of BCG efficacy (0 and 75%) reported from experimental studies and field trials in cattle by different researchers from different countries [reviewed by ( 19 , 21 )], the use of 100% positive seeders as a source of infection could have contributed to the lower efficacy value recorded, as compared with those studies conducted in Mexico, New Zealand, and Chile.…”
Section: Discussioncontrasting
confidence: 67%
“…The animal and public health risks dictate that controls warrant implementation. The lack of funding to underpin a test and slaughter control program in Ethiopia, in common with other low-and middle-income countries (16), means that vaccination is an attractive alternative where the disease is endemic at high prevalence (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…But in general, it was observed that both gross and microscopic pathology were relatively less severe in vaccinated calves than in non-vaccinated calves. Substantiating this observation, a recently conducted meta-analysis suggested that BCG vaccination may help in accelerate control of bTB in endemic settings by inducing immunity against M. bovis and also limiting the progress TB lesion at the site of infection ( 33 ).…”
Section: Discussionmentioning
confidence: 99%